On Ways of Expressing Persuasion in Discourse - Ghaltkhchyan, Siranoush (Armenian Folia Anglistika, 2009)
Persuasion is every planned attempt in communication which aims to impact the interlocutor’s thought or behavior and to change his/her viewpoint or conviction. It aims to force to some action. The article attempts to investigate the speech act of persuasion as a psychological phenomenon and as a subject of functional-linguistic examination which aims to reveal the characteristics of the speech act of persuasion and present the necessary and sufficient conditions which will make the speech act more effective.The article studies the key components of communication, as well as their role in the application of the speech act of persuasion. Special attention is paid to the linguistic and extralinguistic means which make